Political Communications Model for Women in Indonesia In Winning Regional Elections Against The Domination of Male Leadership - Santoso, Puji; Novrica Sinaga, Corry (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This research examines strategies and models of women's political communication in East Java, focusing on the case of Khofifah Indar Parawansa, a prominent figure from Nahdlatul Ulama (NU). Despite losing two consecutive gubernatorial elections, she successfully secured victory in 2018. Using a qualitative approach grounded in a constructivist paradigm, this study analyzes primary data collected through field research, website reviews, and in-depth interviews with relevant informants. The findings highlight the critical role of NU's charismatic clerics (Kyai) in mobilizing support for Khofifah's campaign. This study underscores the importance of political education for Indonesian women, emphasizing effective communication with religious leaders to navigate male-dominated governance at both local and national levels. Kajian ini meneliti strategi dan model komunikasi politik wanita di Jawa Timur, dengan fokus pada kes Khofifah Indar Parawansa, seorang tokoh terkemuka dari Nahdlatul Ulama (NU). Walaupun mengalami kekalahan dalam dua pilihan raya gabenor berturut-turut, beliau berjaya meraih kemenangan pada tahun 2018. Menggunakan pendekatan kualitatif berasaskan paradigma konstruktivis, kajian ini menganalisis data utama yang dikumpulkan melalui penyelidikan lapangan, ulasan laman web, dan wawancara mendalam dengan informan yang berkaitan. Hasil kajian menekankan peranan penting ulama karismatik NU (Kyai) dalam menggerakkan sokongan terhadap kempen Khofifah. Kajian ini menyoroti kepentingan pendidikan politik untuk wanita Indonesia, dengan memberi penekanan pada komunikasi yang berkesan dengan pemimpin agama bagi menghadapi cabaran dalam pentadbiran yang didominasi lelaki di peringkat tempatan dan nasional.